Add-On Therapy with Traditional Chinese Medicine Improves Outcomes and Reduces Adverse Events in Hepatocellular Carcinoma: A Meta-Analysis of Randomized Controlled Trials. (7th June 2017) - Yang, Zongguo; Liao, Xian; Lu, Yunfei; Xu, Qingnian; Tang, Bozong; Chen, Xiaorong; Yu, Yongchun
Abstract : Background and Aims. Traditional Chinese medicine (TCM) therapy for hepatocellular carcinoma remains controversial. This study aimed to evaluate the efficacy and safety of TCM regimens in HCC treatment. Methods . Randomized controlled trials (RCTs) up to June 1, 2016, of the TCM treatment for hepatocellular carcinoma were systematically identified in PubMed, CNKI, Ovid, Embase, Web of Science, Wanfang, VIP, CBM, AMED, and Cochrane Library databases. Results. A total of 1010 and 931 patients in 20 RCTs were randomly treated with add-on TCM therapy and conventional therapy, respectively. The additional use of TCM significantly improved six-month, one-year, two-year, and three-year overall survival rates in HCC cases (RR = 1.3, P = 0.01 ; RR = 1.38, P = 0.0008 ; RR = 1.44, P < 0.0001 ; RR = 1.31, P = 0.02, resp.). Add-on TCM therapy significantly increased PR rate and total response rate (tRR) and reduced PD rate compared to those in control group (34.4% versus 26.3%, RR = 1.30, P = 0.002 ; 41.6% versus 31.0%, RR = 1.30, P < 0.0001 ; and 16.6% versus 26.5%, RR = 0.64, P < 0.0001, resp.). Additionally, TCM combination therapy significantly increased the quality of life (QOL) improvement rate and reduced adverse events including leukopenia, thrombocytopenia, anemia or erythropenia, liver injury, and gastrointestinal discomfort in HCC patients (all P < 0.05 ). Conclusion. Add-on therapy with TCM could improve overall survival, increase clinical tumor responses, lead to better QOL, and reduce adverse events in hepatocellular carcinoma.